Burden of nonsteroidal anti-inflammatory and antiplatelet drug use in Asia: a multidisciplinary working party report - Chan, F.K.; Goto, S.; Wu, M.S.; Abola, M.T.; Yeoh, K.G.; Sutrisna, B.; Chua, S.S.; Mahachai, V.; Turajane, T.; Wu, B.; Zeng, Q.Y.; Sugano, K. (2012)
BACKGROUND & AIMS: We established a working group to examine the burden of atherothrombotic and musculoskeletal diseases in Asia and made recommendations for safer prescribing of nonsteroidal anti-inflammatory drugs (NSAIDs) and low-dose aspirin. METHODS: By using a modified Delphi process, consensus was reached among 12 multidisciplinary experts from Asia. Statements were developed by the steering committee after a literature review, modified, and then approved through 3 rounds of anonymous voting by using a 6-point scale from A+ (strongly agree) to D+ (strongly disagree). Agreement (A+/A) by >/= 80 of panelists was defined a priori as consensus. RESULTS: We identified unique aspects of atherothrombotic and musculoskeletal diseases in Asia. Asia has a lower prevalence of degenerative arthritis and coronary artery disease than Western countries. The age-adjusted mortality of coronary artery disease is lower in Asia; cerebrovascular accident has higher mortality than coronary artery disease. Ischemia has replaced hemorrhage as the predominant pattern of cerebrovascular accident. Low-dose aspirin use is less prevalent in Asia than in Western countries. Traditional Chinese medicine and mucoprotective agents are commonly used in Asia, but their efficacy is not established. For Asian populations, little is known about complications of the lower gastrointestinal tract from use of NSAIDs and underutilization of gastroprotective agents. Our recommendations for preventing ulcer bleeding among users of these drugs who are at high risk for these complications were largely derived from Asian studies and are similar to Western guidelines. CONCLUSIONS: By using an evidence-based, multidisciplinary approach, we have identified unique aspects of musculoskeletal and atherothrombotic diseases and strategies for preventing NSAID-related and low-dose aspirin-related gastrointestinal toxicity in Asia.